Think Pair Share Strategy Supports Student Engagement in Islamic Education Lessons - Pajri, Sahrul; Sai'dy, Sai'dy; Azizah, Nurul; Saputra, M. Indra; Asyha, Agus Faisal (Indonesian Journal of Innovation Studies, 2025)
General Background: Student engagement is critical in ensuring effective learning outcomes, particularly in cooperative learning settings. Specific Background: The Think Pair Share (TPS) strategy has been recognized for promoting active participation, especially in student-centered pedagogies. Knowledge Gap: However, limited empirical studies have explored the application of TPS within the context of Islamic Education (IE), which is often delivered through normative, didactic methods. Aims: This study investigates the effectiveness of the TPS strategy in enhancing students’ learning activeness in IE classes at SMP Negeri 16 Bandar Lampung. Results: Employing a quasi-experimental design, the study found no statistically significant difference between the TPS and control groups in learning activeness (Sig. 2-tailed = 0.104, > 0.05). Novelty: The research highlights contextual limitations—including students' unfamiliarity with interactive models, the brief duration of the intervention, and the normative character of IE content—as possible inhibitors to TPS effectiveness. Implications: Although the TPS model did not yield statistically significant results in this case, it remains a valuable pedagogical tool for fostering collaboration and engagement. Future studies should consider prolonged implementation and strategic alignment between TPS elements and the characteristics of IE content to optimize impact. Highlights: TPS promotes collaboration but may not suit all subject contexts. Short intervention and lack of familiarity limit its impact. Alignment with content and extended use is recommended. Keywords: Think Pair Share, Learning Activeness, Islamic Education, Cooperative Learning, Student Engagement